2003
DOI: 10.1002/hed.10335
|View full text |Cite
|
Sign up to set email alerts
|

The expression of key cell cycle markers and presence of human papillomavirus in squamous cell carcinoma of the tonsil

Abstract: Abstract:Background. Chemical carcinogens induce squamous cell carcinoma (SCC) of the head and neck by targeting the p53 and the retinoblastoma (pRb) pathways. Human papillomavirus (HPV) might have an etiologic role in these cancers at particular sites. Few studies have compared cell cycle protein expression in HPV-positive and HPV-negative tumors in this region.Methods. Fifty tonsil SCCs were analyzed for HPV by PCR and for expression of cell cycle proteins (p53, pRb, p16, p27 KIP1 , and cyclinD1) by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
94
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 29 publications
11
94
2
1
Order By: Relevance
“…We noticed that the tumors with the low expression levels of pRb showed the overexpression of p16 INK4A . Accumulation of this latter protein has been strongly associated with the presence of oncogenic HPV in oropharyngeal carcinomas, 7,10,14,15 which was also evident in the underlying study. These HPV16-positive tonsillar squamous cell carcinomas furthermore showed the downregulation of cyclin D1, next to the accumulation of p14 ARF and p21 Cip1/WAF1 .…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…We noticed that the tumors with the low expression levels of pRb showed the overexpression of p16 INK4A . Accumulation of this latter protein has been strongly associated with the presence of oncogenic HPV in oropharyngeal carcinomas, 7,10,14,15 which was also evident in the underlying study. These HPV16-positive tonsillar squamous cell carcinomas furthermore showed the downregulation of cyclin D1, next to the accumulation of p14 ARF and p21 Cip1/WAF1 .…”
Section: Discussionsupporting
confidence: 65%
“…In our study, p53 overexpression was observed in little more than half of all tonsillar carcinomas, which is consistent with other studies. 7,42 Immunostaining of all other cell cycle proteins was evident in less than 50% of tumors. We noticed that the tumors with the low expression levels of pRb showed the overexpression of p16 INK4A .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations